1983
DOI: 10.1111/j.1744-7348.1983.tb02698.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Indian peanut clump, a soil‐borne virus disease of groundnuts (Arachis hypogaea) in India*

Abstract: A disease characteriscd by severely stunted pl~nts with small dark green Icaveb was found in groundnut (Arachis h y p g a~a l in sandy soils in Punjab State. India. The disease occurred in patches in the field and reappeared in the same positions in succeeding groundnut crops. Plants infected early did not produce mature pods. Seeds sown in soil collected from infected fields produced plants with typical disease symptoms. Phaseolus vulgaris cv. Local and Chenopodium quinoa were found to be good diagnostic host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…249 and 184 nm) (Reddy et al, 1983) which contain RNA ofmol, wt. 1.9 x 106 (RNA-1) and 1.6 x 106 (RNA-2) respectively (D. V. R. Reddy, D. J.…”
Section: (Accepted 18 February 1985)mentioning
confidence: 99%
See 1 more Smart Citation
“…249 and 184 nm) (Reddy et al, 1983) which contain RNA ofmol, wt. 1.9 x 106 (RNA-1) and 1.6 x 106 (RNA-2) respectively (D. V. R. Reddy, D. J.…”
Section: (Accepted 18 February 1985)mentioning
confidence: 99%
“…Robinson & B. D. Harrison, unpublished). Its particles are similar in size, but serologically unrelated, to those of peanut clump virus (PCV) from West Africa (Reddy et al, 1983). Moreover, there is evidence that both viruses are transmitted by Polymyxa graminis (Thouvenel & Fauquet, 1981 a;D.…”
Section: (Accepted 18 February 1985)mentioning
confidence: 99%
“…(Thouvenel & Fauquet, 1981). There is a second probable furovirus of groundnut, Indian peanut clump virus (IPCV), which has rod-shaped virions of similar size to those of PCV and an apparently bimodal genome (Reddy et al, 1983). Although PCV and IPCV are not serologically related, recent sequence analysis (Wesley et al, 1994) has revealed that the coat protein of IPCV is 61% identical to that of PCV.…”
Section: Introductionmentioning
confidence: 99%
“…The Ziegler et al, 1985). Likewise, an Indian isolate of peanut clump virus (IPCV) has been characterized (Reddy et al, 1983) by in vitro translation (Mayo & Reddy, 1985). WSBMV has been extensively studied (Tsuchizaki et al, 1975;Brakke, 1977;Shirako & Brakke, 1984a, b;Hsu & Brakke, 1985;Shirako & Ehara, 1986) and a considerable amount of information concerning the genomic organization of the virus has been deduced.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of physicochemical properties and the genomic organization of WSBMV, BNYVV and IPCV indicates that these viruses are indeed similar and share features consistent with characteristics of the furovirus group. WSBMV and IPCV, in particular, are morphologically and physicochemically very similar (Shirako & Brakke, 1984a;Brakke, 1977;Tsuchizaki et al, 1975;Reddy et aL, 1983;Mayo & Reddy, 1985) and have a common vector, Polymyxa graminis Led. (Estes & Brakke, 1966;Rao & Brakke, 1969;Brakke et al, 1965;Reddy et al, 1983).…”
Section: Introductionmentioning
confidence: 99%